META-INSTI: metabolic adverse events following integrase strand transfer inhibitor administration in spontaneous adverse event reports - Milena M Murray; Lara Fakhouri; Spencer E Harpe (Drugs in Context, 2023)
Background: Metabolic effects of integrase strand transfer inhibitors (INSTIs) have been reported. The FDA Adverse Event Reporting System (FAERS) is a publicly available database that captures spontaneously reported adverse events. The objective of this study was to evaluate the relationship between INSTIs and metabolic adverse events using the FAERS database.